(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The study was conducted to see the impact of social intelligence and adjustment on quality of life among aged persons. For this purpose 250 aged persons with the average age ranged of 65 years were purposively taken from Rosera sub-divisional area of Samastipur district in Bihar state. Social Intelligence Scale of Mathur, Adjustment Inventory of M. Shamshad and K. Jehan and Quality of Life Scale of Kausik & Jaggi were used to collect data. The collected data was analysed with statistical technique. The findings revealed that (i) Quality of life is positively related to social intelligent related factor, (ii) Socially intelligent individuals have better life quality than those of respondents of socially non-intelligent individuals.